Pelatihan Penyusunan Proposal Penelitian Tindakan Kelas (PTK) Berorientasi Pada Proyek Penguatan Profil Pelajar Pancasila (P5) Bagi Guru-Guru SDI Miftahul Hikmah, Blooto Mojokerto - Irham Miftakhul Jannah; Yunita Dwi Wikandari; Sonya Brinda (Politeknik Kampar, 2023)
The project to strengthen the profile of Pancasila in the Kurikulum Merdeka is a learning process that aims to strengthen the character of students in forming and developing positive traits, moral values, ethics, and good attitudes and behavior in individuals according to the precepts in Pancasila. The application of project-based learning is not much different from intra-curricular activities. Sometimes there are obstacles or failures in this project to strengthen the Pancasila profile. So there needs to be research based on the problems of this project-based learning. And one of the appropriate research designs is Classroom Action Research. SDI Miftahul Hikmah, has implemented Kurikulum Merdeka. And experienced several obstacles in its application, especially in this P5 activity. So that the FKIP Community Service team at Mayjen Sungkono University offered a solution for training in preparing class action research proposals (CAR) oriented towards strengthening the Pancasila student profile (P5) for SDI Miftahul Hikmah teachers, Blooto Mojokerto.